2021
DOI: 10.1515/revac-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and extraction routes of allelochemicals from plants and microbes: A review

Abstract: Allelopathy, a complex phenomenon has unveiled both stimulatory and inhibitory effects in plant processes that are mediated by the release of certain chemical compounds commonly known as allelochemicals. Allelochemicals, a form of bioactive secondary metabolites are produced by a diverse group of plants and microbes in response to biotic and abiotic stress. It ranges from a simple hydrocarbon to complex polycyclic aromatic compounds like phenol, flavonoids, tannins, steroids, amino acids, alkaloids and quinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 102 publications
0
16
0
1
Order By: Relevance
“…Bioactive secondary metabolites with allelopathic effects on other plants are termed allelochemicals, which can be found in different parts of plants: roots, leaves, stems, bark, fruits, flowers, and seeds [6]. These allelochemicals obtained from plants belong to diverse chemical groups like alcohols, fatty acids, phenolics, flavonoids, terpenoids, and steroids [7,8]. When released into the environment, allelochemicals can inhibit the germination, growth, and development of adjacent plants by disrupting physiological mechanisms including photosynthesis, respiration, membrane permeability, cell extension, cell division, and water and nutrient uptake [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive secondary metabolites with allelopathic effects on other plants are termed allelochemicals, which can be found in different parts of plants: roots, leaves, stems, bark, fruits, flowers, and seeds [6]. These allelochemicals obtained from plants belong to diverse chemical groups like alcohols, fatty acids, phenolics, flavonoids, terpenoids, and steroids [7,8]. When released into the environment, allelochemicals can inhibit the germination, growth, and development of adjacent plants by disrupting physiological mechanisms including photosynthesis, respiration, membrane permeability, cell extension, cell division, and water and nutrient uptake [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that allelopathy affects plant communities and alters interspecific interactions, either by directly affecting plant growth and development or by indirectly affecting decomposition and soil fertility via soil organisms [5,[9][10][11][12]. Allelopathy modulates plants by interfering with germination, growth, reproduction, and distribution [13]. The grassland ecosystem is one of the largest in the world; it provides vital services such as livestock forage production and has been the focus of allelopathy studies [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that allelopathic compounds extracted from donor plants may significantly reduce seed germination and seedling growth in recipient plants in a concentration-dependent manner [23,[34][35][36][37]. Other authors stated that allelochemicals released by donor plants exerted positive effects on recipient plants at low concentrations, but were phytotoxic above certain threshold doses [13,34]. This pattern may be characteristic of the hormesis effect, in which the allelochemical is stimulatory at low concentrations but inhibitory at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis of the differences in microbial community functions revealed that fatty acid metabolic capability improved in GE plots. Many fatty acids, such as hexadecanoic acid, hexadecenoic acid, octadecanoic acid, and octadecenoic acid, are allelopathic agents ( Iqbal et al, 2019 ; Kong et al, 2019 ), which are derived from decomposed litter, root exudates, and stemflows and negatively affect shrubs and the seedlings of other plants ( Singh et al, 2021 ). GE contributed to vegetation recovery by increasing the metabolic capacity of microbes for allelochemicals, which may partly explain the invasion and expansion of shrubs after the removal of grazing pressure ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%